Anxious Profile Influences Behavioral and Immunohistological Findings in the Pilocarpine Model of Epilepsy - Kohek, Silvia Regina Bica; Foresti, Maira Licia; Blanco, Miriam Marcela; Cavarsan, Clarissa Fantin; Silva, Clivandir Severino da; Mello, Luiz E. (Frontiers in Pharmacology, 2021)
Anxiety and epilepsy have a complex bidirectional relationship, where a depressive / anxious condition is a factor that can trigger seizures which in turn can aggravate the depressive / anxious condition. In addition, brain structures such as the hippocampus and amygdala might have a critical relevance in both epilepsy and anxiety. The aim of the present work was to investigate the influence of different anxious profiles to epileptogenesis. Initially, animals were screened through the elevated plus-maze anxiety test, and then seizure development was evaluated using the pilocarpine model of epilepsy. There were no differences in the susceptibility to status epilepticus, mortality rate or frequency of spontaneous recurrent seizures between animals characterized as anxious as compared to the non-anxious animals. Next, we evaluated immunohistological patterns related to seizures and anxiety in various related brain areas. Despite a decrease in the density of neuropeptide Y and parvalbumin expression in epileptic animals, those presenting greater neuropeptide Y immunoreactivity in various brain regions, also showed higher spontaneous recurrent seizures frequency. Differences on the anxious profile showed to interfere with some of these findings in some regions. In addition, animals that were injected with pilocarpine, but did not develop status epilepticus, had behavioral and neuroanatomical alterations as compared to control animals, indicating its importance as an additional tool for investigating the heterogeneity of the epileptogenic response after an initial insult. This study allowed to better understand the association between anxiety and temporal lobe epilepsy and might allow for therapeutic targets to be developed to minimize the negative impacts associated with it.